Deciphering the chemical phenotype in Atta laevigata (Smith, 1858) (Hymenoptera: Formicidae): A relationship between polymorphism and cuticular hydrocarbons - Santos, Poliana Galvão dos; Santos, Elane Galvão dos; Guimarães, Ingrid de Carvalho; Michelutti, Kamylla Balbuena; Cardoso, Claudia Andrea Lima; Antonialli-Junior, William Fernando (Papéis Avulsos de Zoologia, 2022)
In the Attina subtribe the division of labor among workers is based on different tasks performed by morphological subcastes. Considering that cuticular chemical compounds play important roles as protection against water loss and mediates interactions between nestmates, and that studies on the cuticular chemical profile of ants of the genus Atta are still scarce, the aim of this study was to evaluate the relationship between morphological and chemical phenotypes in the subcastes of Atta laevigata (Smith, 1858) workers. The cuticular chemical composition of the different subcastes was assessed by Gas Chromatography coupled to Mass Spectrometry technique. The compounds found in the cuticle of the different subcastes had carbon chain size between 18 and 31 atoms, with higher content of linear alkanes in workers and soldiers and higher content of branched alkanes in gardeners and generalists, probably related to the type of tasks they perform in their colonies, since some workers perform more intra- or extranidal tasks in relation to others. The results show significant qualitative differences in the cuticular composition of the different subcastes, with a greater relationship between them according to the environmental restrictions that each subcaste is more subjected to due to the role played in the colony.